Rainwater chemistry in a subtropical high-altitude mountain site, South China: Seasonality, source apportionment and potential factors. (1st January 2022) - Li, Jing; Wu, Huawu; Jiang, Pengju; Fu, Congsheng
Abstract: Long-term and frequent observation of rainwater chemistry provides an opportunity to explore the evolution of air pollutant emissions and the effectiveness of the emission control measures. This study presents variations in rainwater chemistry, possible sources of air pollutant emissions, and wet deposition fluxes of ionic species in the rainfall samples during 2018–2020 at Mt. Lushan located in South China. Results showed that the annual volume-weighted mean (VWM) pH of rainwater was 5.8. Moreover, the VWM of 87.7% rainwater samples had pH values above 5.6, which indicated that the atmospheric pollution at Mt. Lushan had less effect during the study period. The polytonic nitrate ion (NO3 − ), the doubly charged positive calcium ion (Ca 2+ ) and the ammonium ion (NH4 + ) were the dominant ions in rainwater where Ca 2+ and NH4 + were the main neutralizing ionic species for rainwater acidity. The highly seasonal variability of ionic concentrations in rainwater was observed among different ionic species, which is closely associated with meteorological conditions and anthropogenic emissions present in the various seasons. Annual wet deposition flux showed an increasing trend during the entire periods. Hence, the wet flux of NO3 − (76.3 kg ha −1 yr −1 ) was three times higher than the annual wet deposition flux of sulfate (SO4 2−, 21.7 kg ha −1 yr −1 ), which points to the fact that acid deposition is still a severe environmental issue in the Mt. Lushan region. Positive matrix factorization (PMF) and correlation matrix were used to identify five sources for ionic species, including aging sea salt, fossil fuel combustion, agriculture, dust, and biomass burning. These findings could be helpful in establishing emission control policies to protect and manage pollution control in the eco-environment in South China. Highlights: The annual volume-weighted mean (VWM) pH of rainwater was 5.8 Ca 2+ and NH4 + were the main neutralizing ionic species for rainwater acidity. Five sources of rainwater ionic species identified by PMF analysis. Nitrogen deposition is still a severe environmental issue in the Mt. Lushan region.